Purkinje cells of the cerebellum control deceleration of tongue movements. - Paul Hage; Mohammad Amin Fakharian; Alden M Shoup; Jay S Pi; Ehsan Sedaghat-Nejad; Simon P Orozco; In Kyu Jang; Vivian Looi; Hisham Y Elseweifi; Nazanin Mohammadrezaei; Alexander N Vasserman; Toren Arginteanu; et al. (PLoS Biology)
We use our tongue much like our hands: to interact with objects and transport them. For example, we use our hands to sense properties of objects and transport them in the nearby space, and we use our tongue to sense properties of food morsels and transport them through the oral cavity. But what does the cerebellum contribute to control of tongue movements? Here, we trained head-fixed marmosets to make skillful tongue movements to harvest food from small tubes that were placed at sharp angles to their mouth. We identified the lingual regions of the cerebellar vermis and then measured the contribution of each Purkinje cell (P-cell) to control of the tongue by relying on the brief but complete suppression that they experienced following an input from the inferior olive. When a P-cell was suppressed during protraction, the tongue's trajectory became hypermetric, and when the suppression took place during retraction, the tongue's return to the mouth was slowed. Both effects were amplified when two P-cells were simultaneously suppressed. Moreover, these effects were present even when the pauses were not due to the climbing fiber input. Therefore, suppression of P-cells in the lingual vermis disrupted the forces that would normally decelerate the tongue as it approached the target. Notably, the population simple spike activity peaked near deceleration onset when the movement required precision (aiming for a tube), but not when the movement was for the purpose of grooming. Thus, the P-cells appeared to signal when to stop protrusion as the tongue approached its target.